Influence of phonics teaching on young EFL learners´ pronunciation - Matos, Ana Elisa Barradas de (2021)
This study investigates the influence of phonics teaching on young EFL learners’ pronunciation of the phonemes /dʒ/, /ʃ/, /tʃ/, /θ/, /h/ and /w/. The research project was carried out in a private primary school, over a period of three months and involved 16 learners from year 4. The data was gathered through pre-study and poststudy audio recordings, pre-study and post-study assessment worksheets and a teacher’s journal. Phonics instruction was provided to participants, after the implementation of the pre-study data collection tools. The phonics teaching included songs, gestures, tongue-twisters and activities to promote the identification of the phonemes in relation to their orthographic representations. The assessment worksheets and the audio recordings were analysed quantitively to verify how many learners could recognise and produce accurately the sounds addressed by this research. The weekly entries in the teacher’s journal were analysed qualitatively. Results show that raising learners’ awareness to phonemes and the use of phonics instruction can have a positive impact on the pronunciation of young EFL learners.